Eutectic mixtures based on polyalcohols as sustainable solvents: screening and characterization - Silva, Liliana P. (2018)
Despite some promising potential applications of eutectic systems containing choline chloride ([Ch]Cl) and a polyalcohol, a detailed investigation of the thermodynamic behavior of these systems is still missing. In this work, the solid-liquid equilibria phase diagrams of binary systems containing [Ch]Cl and one from six different polyalcohols (ethylene glycol (EG), 1,3-propanediol, glycerol (Gly), meso-erythritol, xylitol, and sorbitol) were measured in the full composition. Except for the mixtures with Gly or EG, a quasi-ideal behavior in the [Ch]Cl solubility curve is observed. In the polyalcohol solubility curve, the mixtures present small negative deviations from ideality, except for [Ch]Cl + EG, which is slightly positive. The solid-liquid phase diagrams show a large liquid composition window, and not a fixed stoichiometry for the eutectic points, where the mixtures can be used as solvents close to, or below, room temperature. Aiming at their application, viscosities and densities were measured at the eutectic point in the temperature range from 278.15 to 373.15 K. All systems present densities and viscosities higher than water, which is directly related to the strong interactions between the components. Solvatochromic parameters were measured to characterize the solvents, and they show that solvent tunability can be achieved by varying the polyalcohol mole fraction.